The anti-leukemia activity and mechanisms of shikonin: a mini review - Dong, Han; Chang, Chun-Di; Gao, Fei; Zhang, Na; Yan, Xing-Jian; Wu, Xue; Wang, Yue-Hui (Frontiers in Pharmacology, 2023)
Leukemia encompasses a group of highly heterogeneous diseases that pose a serious threat to human health. The long-term outcome of patients with leukemia still needs to be improved and new effective therapeutic strategies continue to be an unmet clinical need. Shikonin (SHK) is a naphthoquinone derivative that shows multiple biological function includes anti-tumor, anti-inflammatory, and anti-allergic effects. Numerous studies have reported the anti-leukemia activity of SHK during the last 3 decades and there are studies showing that SHK is particularly effective towards various leukemia cells compared to solid tumors. In this review, we will discuss the anti-leukemia effect of SHK and summarize the underlying mechanisms. Therefore, SHK may be a promising agent to be developed as an anti-leukemia drug.